Optimization Strategies in Non-Contrast Head CT Examinations for Patients Based on The Role of Radiographers and Clinical Protocols: A Literature Review - Nuramalia, Putri Pradita; Irsal, Muhammad; Sutoro, Shinta Gunawati; Supriyaningsih, Eny; Rizqi, Muhammad; Hartati, Sri (Ahmar Metastasis Health Journal, 2025)
Non-contrast head computed tomography (CT) examinations are associated with a potential risk of unnecessary radiation exposure when optimization principles are not consistently applied in clinical practice. Radiographers play a pivotal role in implementing appropriate clinical protocols to ensure patient radiation safety without compromising diagnostic image quality. This study aimed to review optimization strategies for non-contrast head CT examinations with a particular focus on the role of radiographers and clinical protocols. Literature review was conducted using articles retrieved from the PubMed database published between 2020-2025. The selected studies were analyzed descriptively by examining study characteristics, optimization approaches, and their implications for clinical radiography practice of non-contrast head CT examination. The results indicate that optimization of non-contrast head CT can be achieved through appropriate adjustment of technical parameters by radiographers, application of iterative reconstruction techniques, minimization of patient positioning errors in anteroposterior, posteroanterior, and lateral orientations, use of eye shielding combined with tube current modulation (TCM), and implementation of diagnostic reference levels (DRLs) based on clinical indications. In addition, regular radiographer training contributes to the consistent application of optimization strategies. In conclusion, effective optimization of non-contrast head CT examinations requires an integrated approach that combines radiographer competency and evidence-based clinical protocols to minimize patient radiation exposure while maintaining diagnostic image quality.